RNA synthesis of vesicular stomatitis virus. VII. Complete separation of the mRNA's of vesicular stomatitis virus by duplex formation. - Freeman, G J (1977)
Full-length virion RNA and complementary mRNA's of vesicular stomatitis virus can be annealed to each other, digested with RNases, and then separated as five unique duplex RNA molecules on polyacrylamide slab gels. Similar RNA duplexes were detected whether mRNA or virion RNA was the radioactive component and whether the mRNA was synthesized in vitro or in vivo. The sharp banding pattern of these RNA molecules was dependent on treatment with RNase T2, suggesting that removal of poly(A) is necessary. Identification of the coding region contained in each RNA duplex was based on their previous identification as single-stranded mRNA on formamide-containing, polyacrylamide gels. Because the two smallest mRNA'S had not been previously separated, their identification was based on their in vitro transcriptional gene order. In the order of increasing mobilities on the slab gels, the RNA duplexes are identified as the hybrid of the region of the genome RNA hybridized to the complementary mRNA coding for the large protein, the glycoprotein, the nucleocapsid protein, the core-associated NS protein, and the matrix protein (L,G,N,NS, and M). Several lines of evidence support the presence of undegraded complete mRNA, excluding poly(A), in these RNA duplexes. Also, the two smallest mRNA's, separated by duplex formation, were denatured, and their individual oligonucleotide fingerprints were determined. From chemical length determinations, the molecular weights of the mRNA, minus poly(A), are 2.78 X 10(5) and 2.5 X 10(5), respectively, for the mRNA's of the NS and M proteins.